1999
DOI: 10.1074/jbc.274.28.19814
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of a Vascular Smooth Muscle Cell NAD(P)H Oxidase by Thrombin

Abstract: Thrombin is a potent vascular smooth muscle cell (VSMC) mitogen. Because recent evidence implicates reactive oxygen intermediates (ROI) in VSMC proliferation in general and atherogenesis in particular, we investigated whether ROI generation is necessary for thrombin-induced mitogenesis. Treatment of human aortic smooth muscle cells with thrombin increased DNA synthesis, an effect that was antagonized by diphenyleneiodonium but not by other inhibitors of cellular oxidase systems. This effect of thrombin was acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 309 publications
(74 citation statements)
references
References 55 publications
4
68
0
2
Order By: Relevance
“…The flavoproteincontaining enzyme inhibitor Diphenyleneiodonium (DPI) has been widely used to evaluate the activity of this pathway. DPI has been shown to inhibit Ang II, thrombin and PDGF mediated induction of ROS production in VSMC (31,34,35). When cells were pretreated with 10 µM DPI prior to stimulation with Ang II, HIF-1α induction was completely inhibited (Fig.…”
Section: Interestingly Recent Results Have Suggested a Possible Rolementioning
confidence: 99%
See 3 more Smart Citations
“…The flavoproteincontaining enzyme inhibitor Diphenyleneiodonium (DPI) has been widely used to evaluate the activity of this pathway. DPI has been shown to inhibit Ang II, thrombin and PDGF mediated induction of ROS production in VSMC (31,34,35). When cells were pretreated with 10 µM DPI prior to stimulation with Ang II, HIF-1α induction was completely inhibited (Fig.…”
Section: Interestingly Recent Results Have Suggested a Possible Rolementioning
confidence: 99%
“…Recent evidence has convincingly shown that in VSMC, Ang II, thrombin and PDGF can modulate the expression and activity of different elements of the NAD(P)H oxidase system (32)(33)(34)(35)(36). This system is responsible for strong increases in intracellular ROS levels found in these cells after growth factor and hormone stimulation.…”
Section: Reactive Oxygen Species Are Necessary For Ang II Induced Hifmentioning
confidence: 99%
See 2 more Smart Citations
“…This vascular redox regulatory enzyme is of characteristics of phagocyte NOX, which is composed of two transmembrane-bounded catalytic proteins of gp91 phox and p22 phox , and three cytosol-associated subunits of p47 phox , p67 phox and p40 phox . In addition to gp91 phox named as Nox2, some other homologues of gp91 phox such as Nox1, Nox4 and Nox5 were identified in the vascular cells such as endothelial and smooth muscle cells [3,4]. NOX is now well accepted as an important enzyme that produces O 2 .− in the vasculature under physiological and pathological conditions to exert redox regulatory action on vascular function or to produce pathogenic responses.…”
Section: Introductionmentioning
confidence: 99%